Relationship between service quality and satisfaction among patients of UKM Specialist Centre / Hamidah Andong - Andong, Hamidah (Faculty of Business and Management, 2009)
The purpose of this study was to investigate the relationship of the selected independent variables: service quality, relationship commitment and communication strategies with dependent variable which is patient satisfaction. In order to provide a guide in the study, three hypotheses were formulated. Data were collected from 30 patients of UKM Specialist Centre using the questionnaire. Overall, the study revealed that the level of patient satisfaction of UKM Specialist centre’s patient is high. Result obtained from the correlation analysis revealed that all the three variables which are service quality, relationship commitment and communication strategies were moderately or substantially positive related to patient satisfaction. To conclude, this study investigates the relationship between the patient satisfaction and selected independent variable which are service quality, relationship commitment and communication strategies of the study appeared to provide significant results